KISA VE UZUN SÜRELİ AMİTİRİPTİLİN KULLANILMASININ, AMELİYATTA HEMODİNAMİĞE ETKİLERİ - SALİHOĞLU, Ziya (Cerrahpaşa Medical Journal, 2019)
Background.- Amitriptylin is frequently using a tricycle antidepressant. The first effect of amitriptylin is increasing plasma serotonin and epinephrine concentrations, but the concentration decreases later. So, short and long time use of amitryptilin has different effects on hemodynamic parameters. In this study short and long time using of amitriptylin are compared regarding to their effects on hemodynamic parameters intraoperatively. Background.- Amitriptylin is frequently using a tricycle antidepressant. The first effect of amitriptylin is increasing plasma serotonin and epinephrine concentrations, but the concentration decreases later. So, short and long time use of amitryptilin has different effects on hemodynamic parameters. In this study short and long time using of amitriptylin are compared regarding to their effects on hemodynamic parameters intraoperatively. Conclusion.- As a conclusion using of amitriptylin for short or long time periods causes different heamodynamic changes, so anaesthetic management must be performed carefully.